2015
DOI: 10.3892/mmr.2015.3572
|View full text |Cite
|
Sign up to set email alerts
|

Rapid detection of active human cytomegalovirus infection in pregnancy using loop-mediated isothermal amplification

Abstract: Understanding the association between congenital human cytomegalovirus (HCMV) infection and active maternal HCMV infection during pregnancy is important for maternal and neonatal healthcare. In the present study, a loop-mediated isothermal amplification (LAMP) method was established for the detection of CMV DNA from whole blood or amniotic fluid samples, using reverse transcription-quantitative polymerase chain reaction. The results of the present study demonstrated that the CMV LAMP assay detection was specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Since LAMP was reported in 2000 by Notomi, it has been widely applied in nucleic acid analysis because of its simplicity, rapidity, high efficiency, and outstanding specificity 12 . In recent years, this method has been successfully applied in molecular detection and diagnostics of bacterial 16 17 , viral 18 19 , fungal 20 21 22 23 , and parasitic diseases 24 25 in both animals and plants. However, the application of LAMP in fungicide resistance of plant pathogens has not been reported until the detection of benzimidazole-resistant mutants of F. graminearum was disclosed by our group 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Since LAMP was reported in 2000 by Notomi, it has been widely applied in nucleic acid analysis because of its simplicity, rapidity, high efficiency, and outstanding specificity 12 . In recent years, this method has been successfully applied in molecular detection and diagnostics of bacterial 16 17 , viral 18 19 , fungal 20 21 22 23 , and parasitic diseases 24 25 in both animals and plants. However, the application of LAMP in fungicide resistance of plant pathogens has not been reported until the detection of benzimidazole-resistant mutants of F. graminearum was disclosed by our group 26 .…”
Section: Discussionmentioning
confidence: 99%
“…However, Nagamine et al suggested that if circular primers are used, RT-LAMP reaction could be performed in 30 min (26). The study by Wang et al also identified CMV virus at 64 C in 30 min with RT-LAMP reaction (27).…”
Section: Discussionmentioning
confidence: 99%
“…LAMP, a novel DNA amplification technique, is an auto‐cycling and strand displacement DNA synthesis method involving the use of the large fragment of Bst DNA polymerase and a set of 4–6 specific primers (Notomi et al, ; Mori et al, ; Nagamine et al, ; Curtis et al, ; Goto et al, ). Since this technique was developed in 2000, LAMP has been widely used for detection of pathogens of both plants and animals (Duan et al, ,b; Kogovšek et al, ; Lee et al, ; Niu et al, ; Okuda et al, ; Wang et al, ; Zhuo et al, ). However, it has been rarely used for detection of mutations conferring drug resistance in pathogenic microorganisms until recently.…”
Section: Discussionmentioning
confidence: 99%